Health risks in menopausal women with polycystic ovary syndrome - Szkodziak, Piotr; Czuczwar, Piotr; Woźniak, Sławomir; Woźniakowska, Ewa; Paszkowski, Tomasz (Menopause Review/Przegląd Menopauzalny, 2013)
Polycystic ovary syndrome (PCOS) is the most common hormonal disorder in women. According to the National Institutes of Health (NIH), it affects about 10% of women of the reproductive age. When using the Rotterdam Criteria, PCOS is diagnosed in about 15% of the general population. This disorder is considered to be a syndrome because its etiology is complex and still not entirely understood, which leads to the occurrence of various phenotypes in women with PCOS. In more than half of PCOS patients, obesity or overweight is observed, and so is insulin resistance and hyperinsulinism. Excessive prolactin and androgen (including adrenal androgens) levels are also noted. Two widely cited ESHRE/ASRM workshop consensuses have been published: one concerning the diagnosis of PCOS (2004) and the other regarding the management of infertility (2008). Recently, a new third ESHRE/ASRM consensus summarizing the current knowledge on various health aspects in PCOS women has been published (2012). Important health-related issues concerning women in adolescence, as well as during the reproductive and menopausal periods are discussed. These include hirsutism, acne, quality of life, pregnancy complications, long-term metabolic disorders, cardiovascular risk factors and risk of malignancies. This paper summarizes current knowledge about health risks in menopausal women with PCOS.